Exercise-Related Time Course of Pulsatility Index in Brachial Artery Following Forearm Exercise Assessed by Doppler Ultrasound - Osada, Takuya (The Tohoku Journal of Experimental Medicine, 2004)
At rest, vascular reactivity assessed by the changes in pulsatility index (PI) is one indicator of vessel stenosis in some clinical/basic science research. However, all types of vessel stenosis do not show an alteration in the PI, because flow perfusion may be maintained by the development of collateral vessels such as in severe arterial stenosis or non-severe arterial stenosis. Therefore at rest, changes in the PI may not always be a precise indicator of vessel stenosis. However, a few studies have used the PI following exercise, which may provide additional information on hemodynamics. The purpose of the present study was to examine the exercise-related time course of the PI in the brachial artery after ischemic or non-ischemic isometric handgrip exercise (IHE) using Doppler ultrasound, and to determine the potential use of this parameter as an indicator of vascular disease. Ten healthy young male subjects performed IHE at 10% and 30% of maximum voluntary contraction (MVC) for 2-minutes (min) with or without arterial occlusion (AO), or 2-min of AO alone. Following each 2-min session, PI was determined during the 5-min recovery period. A significant difference in the recovery PI was observed between IHE, ischemic IHE, as well as AO alone. Exercise with AO significantly increased the reduction in the PI compared to exercise alone, or AO alone, at both 10% and 30%MVC. These results suggest, exercise-induced changes in the time course of the PI during recovery may potentially be a useful diagnostic tool. Exercise-induced ischemic state may potentially be a useful indicator for detecting arteriovascular disease, even if it is not detected by AO alone.